Aaron Slater and the sneaky snake - Beaty, Andrea (Beaty, Andrea. Questioneers, 2023)
When Zookeeper Fred's green snake Vern gets loose in the zoo, the Questioneers need all their talents to help find him, but in the end, it is Aaron's art that leads the way. Includes facts about snakes.